Rumen fermentation and nutrient flow to the omasum in Holstein cows fed extruded canola seeds treated with or without lignosulfonate - Wallacy Barbacena Rosa dos Santos (Revista Brasileira de Zootecnia, 2012)
Four multiparous Holstein cows averaging 548 kg of body weight and 74 d in lactation were used in a Latin square design with four 21-d experimental periods to determine effects of feeding extruded versus non-extruded canola seed, with or without 50 g/kg lignosulfonate on rumen fermentation, nutrient flow to the omasum, and degradability of dry matter (DM) and N of each diet. The DM effective degradability increased with extrusion and lignosulfonate treatment had no effect. The effective degradability of N was similar between diets. Lignosulfonate treatment of extruded versus non-extruded canola seeds decreased ruminal and total tract apparent digestibility of organic matter. The lowest apparent ruminal and highest intestinal digestibilities of protein, expressed as a percentage of N intake were observed for cows fed extruded canola seeds without lignosulfonate. Lignosulfonate treatment and extrusion had no effect on pH and concentrations of ammonia N and volatile fatty acids in the rumen. Results suggest that extruded canola seed untreated with formaldehyde may stimulate efficiency of microbial protein synthesis and is an effective means of increasing the availability of protein in the small intestine without affecting the total tract apparent digestibility of protein.